PRAKTEK SHORT SELLING, MARGIN TRADING, DAN INSIDER TRADING DI PASAR SAHAM DALAM PERSPEKTIF ISLAM - Muhammad Muhajir Aminy (UIN Mataram, 2018)
Stock trading has been allowed in Islam because it does not conflict with Islamic principles. It is similar to other common commodity trading, because in this stock market we can find stock’s seller and buyer, object to be traded, and its market. Not all activities are allowed in stock market according to Islamic law or doesn’t fulfill sharia compliance. Short selling practice in stock market is prohibited because it allows investors to sell stock which they do not have.Margin trading can’t be implemented as an activity in islamic stock market because it relates to interest (usury) which is not allowed in Islam. Meanwhile, insider trading is prohibited in Islam because it indicates fraudulence activity (tadlis) inside the market.